Educación para la salud en las organizaciones escolares - Chamorro Bacilio, Yrene Gloria (2010)
This article focuses on the relationship between education and health, and the relevance of the school in a comprehensive teaching. Specifically, the article develops different conceptions about the health, education, health promotion and healthy lifestyles taking into account the contributions of authoritative sources. In addition to the theoretical approach, the author introduces a reflection about the health education in the Peruvian context.